CDR 2019
DOI: 10.20517/cdr.2019.70
|View full text |Cite
|
Sign up to set email alerts
|

How to conjugate the stemness marker ALDH1A1 with tumor angiogenesis, progression, and drug resistance

Abstract: Cancer is the second leading cause of death worldwide. The survival of cancer patients depends on the efficacy of therapies and the development of resistance. There are many mechanisms involved in the acquisition of drug resistance by cancer cells, including the acquisition of stem-like features. Cancer stem cells (CSCs) represent a major source of tumor progression and treatment resistance. CSCs are a subpopulation of cancer cells having the abilities to self-renew and form spheres in vitro. Aldehyde dehydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 105 publications
(126 reference statements)
0
20
0
Order By: Relevance
“…Among the available colorectal cancer cell lines, HCT116 cells were selected for studying ALDH1B1 enzyme activity because these cells constitutively and highly express ALDH1B1, while they show low ALDH1A1 expression [ 22 ]. As ALDH1A1 is reportedly associated with the stemness of several tumors via RA generation [ 23 ], the use of HCT116 as a host cell line would minimize any confounding effect by ALDH1A1 [ 15 ]. The results showed that the overexpression of ALDH1B1 led to decreased mRNA levels of PTEN , irrespective of whether ALDH1B1 was stably or transiently expressed ( Figure 2 B,C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the available colorectal cancer cell lines, HCT116 cells were selected for studying ALDH1B1 enzyme activity because these cells constitutively and highly express ALDH1B1, while they show low ALDH1A1 expression [ 22 ]. As ALDH1A1 is reportedly associated with the stemness of several tumors via RA generation [ 23 ], the use of HCT116 as a host cell line would minimize any confounding effect by ALDH1A1 [ 15 ]. The results showed that the overexpression of ALDH1B1 led to decreased mRNA levels of PTEN , irrespective of whether ALDH1B1 was stably or transiently expressed ( Figure 2 B,C).…”
Section: Resultsmentioning
confidence: 99%
“…Among several colorectal cancer cell lines, HCT116 was selected for the following reasons. According to a previous study [ 23 ], ALDH1A1 activity is highly associated with the SC properties of some tumors. As with ALDH1B1, ALDH1A1 contributes to cancer stemness, metastasis, and chemoresistance by generating retinoic acids.…”
Section: Methodsmentioning
confidence: 99%
“…We could distinguish genes that were upregulated in hypoxia and stemness pathways in 786-0 R167Q when compared with the 786-0 WT VHL condition. Namely, the expression of ALDH1A1, a well-known stemness marker [28,29], was gradually increased from 786-0 EV-, to WT-and 786-0 R167Q-transfected cells (Figure 4B,C). The same trend was observed for KLF4 and TNC genes, encoding Kruppel-like factor 4 and tenascin C, respectively.…”
Section: Vhl-r167q Mutation Modulates the Expression Of Genes Belonging To Hypoxia And Stemness Pathwaysmentioning
confidence: 97%
“…Aberrant angiogenesis is an important step for cancer progression, which is linked to the tumor growth and metastasis ( 162 ). Aberrant tumor vessels can be a route for highly invasive tumor cells ( 163 ). Such weakly functional tumor vessels promote hypoxia and immunosuppression, thereby causing tumor progression ( 164 ).…”
Section: Factors Influencing (Im)maturity Of Tumor Cellsmentioning
confidence: 99%